What can qualitative studies offer in a world where evidence drives decisions? - Sally Thorne (Elsevier, 2018)
In an environment in which evidence-based practice is the espoused norm, nurses have understandably sought to frame the knowledge they deem relevant to practice decisions, including the findings of their qualitative studies, as a form of evidence. However, since cancer patients face a significant challenge interpreting various evidence claims, it is important to recognize that the results of our qualitative studies reflect a different form of knowledge from that which an evidence-based practice definition of evidence presumes. Thus, we need to rethink our relationship to what qualitative studies offer to the evidentiary dialog. An approach to qualitative inquiry that derives from a nursing disciplinary logic model is, therefore, presented as an alternative means by which to generate the kinds of knowledge nurses need to practice and to gain expertise in clinical wisdom. Drawing on cancer communications research as an example, a nursing angle of vision on how best to use qualitative approaches to interpret evidence and inform practice emerges.